PAKAN ALTERNATIF PADA TRENGGILING JAWA (MANIS JAVANICA DESMAREST, 1822) DI PENANGKARAN - Rianti, Anita; Takandjandji, Mariana (BERITA BIOLOGI, 2019)
The use of alternative feed for Sunda pangolin in captivity is one way to cope with a shortage of feed. The aims of the research was to determine the impact of the use of alternative feed toward feed consumption and daily weight gain of pangolin in captivity. The research was conducted at Research Forest Dramaga, Bogor. The research material used by 4 individual pangolin consists of 2 males and 2 females with an average weight of 4.28 ± 0.22 kg. Research using 4x4 Latin Square Design, with 7 days of preliminary period and 14 days of data collection. The treatment applied were 4 alternative feeding i.e A= 50% kroto + 50% egg; B= 50% kroto + 50% tofu; C= 50% kroto + 20% egg + 30% tofu; D= 50% kroto + 18% egg + 26% tofu + 6% termites. The results showed that the effect of alternative feed not significantly (P<0.05) on feed consumption and body weight gain pangolin. Pangolin with treatment C consumed feed based on dry matter as much as 63.08 grams per day or 10.46% from body weight and the biggest weight gain 35.0 grams per individual per day.